Symmetrical manifestations of the title in Ghassan Wannous Stories - Marroushia, Mohamad; Ismail , Hanaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The contemporary interest has increased with the titles, so that some researchers considered the titles as mini texts which contribute in forming a primary opinion that motivate the reader and guide him to some meaning that the authors referring to, and other researchers considered the titles just a hypothesis for reading, not prejudice, because it might lead the reader towards the meaning directly, and it might deceive and mislead him as well, which make the creative texts poetically bigger and richer, and in both cases the title remains the first textual episode that the reader’s awareness meet with the creative text, regardless the type of the titles: realistic, equivocation, symbolism and others. My choice has fallen into this research because of the variety that Ghassan Wannous text stories’ have shown, which indicates the awareness of the writer about the importance of the titles, and the role it might perform in serving the textual meaning, and this is what this research aspires to approach and highlights.